Biodiversity, distribution, ecology and management of non-native weeds in Mexico: a review - Francisco J. Espinosa-García; José Luis Villaseñor (Revista Mexicana de Biodiversidad)
The current knowledge on the richness, ecology, distribution and management of non-native flowering weeds in Mexico and some data on their possible environmental and economic impact are briefly reviewed. We reviewed 216 refereed publications, most indexed international articles. Most publications refer to management sensu lato (34.9%), floristics (19.5%), ecology (21.5%), and detection of new non-native weeds (13.3%). The most complete research area is floristics, along with species inventories with their incidence at the state level. The publications, although interesting and of high quality, are disjointed and rarely coordinated with decision makers, general public or policy makers. It is estimated that there are about 700 wild non-native species in Mexico; 80% naturalized and we estimate that there are between 58 and 180 invasive weed species that cause environmental or socioeconomic damage. The 700 species represent 2.8% of the 23,000 species of Mexican flora. Although there is no overall estimate of the cost of the losses caused by weeds introduced for Mexico, it is argued that it is high in terms of agriculture, environment and human health. A number of measures are suggested to generate the scientific knowledge needed to prevent and/or sustainably manage invasive weed invasions.